Enantioselective Synthesis of Acenaphthene-Type Monohydrosilanes - Mu, Delong; Zhu, Xinrui; Chen, Jiean (Organic letters, 2025)
Acenaphthene and its analogues are privileged frameworks in medicinal chemistry and material science. However, the properties of silicon-substituted acenaphthene-type scaffolds are poorly understood. Here, we report a rhodium-catalyzed intramolecular C(sp3)–H silylation for enantioselective synthesis of acenaphthene-type scaffolds with excellent enantioselectivity and broad substrate scope. This protocol enables facile access to various quaternary stereogenic silicon centers with heterocyclic scaffolds using monohydrosilanes as chiral building blocks. We also synthesized a new silafluofen analogue that shows good insecticidal activity.